2020
DOI: 10.3390/cancers12113361
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Comparing the Efficacy of Lactate Dehydrogenase Levels Versus Circulating Cell-Free microRNAs in Monitoring Responses to Checkpoint Inhibitor Immunotherapy in Metastatic Melanoma Patients

Abstract: Serum lactate dehydrogenase (LDH) is a standard prognostic biomarker for stage IV melanoma patients. Often, LDH levels do not provide real-time information about the metastatic melanoma patients’ disease status and treatment response. Therefore, there is a need to find reliable blood biomarkers for improved monitoring of metastatic melanoma patients who are undergoing checkpoint inhibitor immunotherapy (CII). The objective in this prospective pilot study was to discover circulating cell-free microRNA (cfmiR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…In regards to the miRNA content, authors found some miRNAs enriched in the EVs from non-responding patients, such as miR-551a; in contrast, other miRNAs such as miR-4519 and miR-4674 were enriched in the EVs derived from responding patients ( 49 ). Finally, a pilot study identified a signature composed of three circulating miRNAs, namely miR-4649-3p, miR-615-3p and miR-1234-3p as potentially capable of distinguishing melanoma patients who better respond to immunotherapy (ipilimumab, nivolumab, pembrolizumab, or the combination of ipilimumab and nivolumab as first line therapy) ( 50 ). In particular, the levels of these miRNAs significantly decreased in the post-treatment samples derived from patients who had a complete response (CR) as compared to patients who progressed from immunotherapy.…”
Section: Non Coding Rnas (Ncrnas)mentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to the miRNA content, authors found some miRNAs enriched in the EVs from non-responding patients, such as miR-551a; in contrast, other miRNAs such as miR-4519 and miR-4674 were enriched in the EVs derived from responding patients ( 49 ). Finally, a pilot study identified a signature composed of three circulating miRNAs, namely miR-4649-3p, miR-615-3p and miR-1234-3p as potentially capable of distinguishing melanoma patients who better respond to immunotherapy (ipilimumab, nivolumab, pembrolizumab, or the combination of ipilimumab and nivolumab as first line therapy) ( 50 ). In particular, the levels of these miRNAs significantly decreased in the post-treatment samples derived from patients who had a complete response (CR) as compared to patients who progressed from immunotherapy.…”
Section: Non Coding Rnas (Ncrnas)mentioning
confidence: 99%
“…Interestingly, the increased levels of one of these miRNA, i.e. miR-615-3p showed a superior statistic capability in predicting PD in post-therapy plasma samples as compared to LDH levels ( 50 ).…”
Section: Non Coding Rnas (Ncrnas)mentioning
confidence: 99%
“…Similarly, other studies have proposed the analysis of the methylation of several genes in plasma as circulating epigenetic biomarkers able to discriminate between healthy controls and patients with AA or CRC [ 165 , 166 ]. In addition, approaches based on methylation microarrays [ 33 ] and NGS [ 167 ] have been used to identify epigenetic biomarkers in ctDNA for cancer detection.…”
Section: Epigenetic Biomarkers In Colorectal Cancermentioning
confidence: 99%
“…Besides, the detection of hypermethylated RASSF1A in serum before treatment was able to predict the prognosis and clinical response to drugs in advanced melanoma patients [ 185 ]. In a recent pilot study using NGS and machine learning, Bustos et al were able to identify a circulating miRNA signature (miR-4649-3p, miR-615-3p, and miR-1234-3p) associated with the response to ICIs in advanced melanoma patients, suggesting that circulating miRNAs could enable real-time monitoring of patients receiving this type of treatment [ 167 ]. The plasmatic levels of other ncRNAs such as lncRNAs (IGF2AS, anti-Peg11, MEG3, Zeb2NAT) were also found to be associated with prognosis and therapy response in BRAF -mutant advanced melanoma patients treated with the BRAF inhibitor vemurafenib [ 186 ].…”
Section: Epigenetic Biomarkers In Other Tumor Types and Multi-cancer Testsmentioning
confidence: 99%
“…In comparison to PCR, NGS requires no specific assay to determine if sarcoma-associated genes are present in clinical material. Analyses using NGS may be unbiased and genome-wide or instead focussed on panels of known oncogenes either as an oncogene-focussed adaptation of standard NGS (FusionPlex (Archer) [ 116 ] or AmpliSeq Focus panel (Illumina) [ 117 ]) or variations based on nuclease protection chemistry (Edgeseq (HTG) [ 118 ]).…”
Section: Liquid Biopsy For Sarcoma Surveillancementioning
confidence: 99%